2022
DOI: 10.1136/bmjopen-2021-056123
|View full text |Cite
|
Sign up to set email alerts
|

Comparing absolute and relative distance and time travel measures of geographic access to healthcare facilities in rural Haiti

Abstract: IntroductionWhile travel distance and time are important proxies of physical access to health facilities, obtaining valid measures with an appropriate modelling method remains challenging in many settings. We compared five measures of geographic accessibility in Haiti, producing recommendations that consider available analytic resources and geospatial goals.MethodsEight public hospitals within the ministry of public health and population were included. We estimated distance and time between hospitals and geogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Although more accurate measures of travel distance exist, studies comparing Euclidean distance, road network distance, and travel time have found a high degree of correlation across many geographic settings [46][47][48] . Surveys of rural VA enrollees have shown that travel distance is the greatest barrier to healthcare access 1 .…”
Section: Travel Burden: Observed and Excess Distancesmentioning
confidence: 99%
“…Although more accurate measures of travel distance exist, studies comparing Euclidean distance, road network distance, and travel time have found a high degree of correlation across many geographic settings [46][47][48] . Surveys of rural VA enrollees have shown that travel distance is the greatest barrier to healthcare access 1 .…”
Section: Travel Burden: Observed and Excess Distancesmentioning
confidence: 99%